IMPLEMENTASI PROGRAM SAFETY RIDING UNTUK KALANGAN PELAJAR OLEH POLRES KAMPAR - Dewi Pela Wulandari; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Transportation is one tool that is needed in human life, one of them is a motorcycle. The increasing use of motorcycles has an impact on the use of highways that are also increasing. Whereas the area of Kampar district is large enough to cause congestion and traffic density problems are growing that causing traffic violations by the society, especially for students. To overcome traffic problems the Police introduce a Program that known as Safety Riding Program (safety driving). This research used type qualitative method with descriptive data assessment. In collecting data, researcher use purposive sampling method as source of information and data analysis with triangulation technique. The results showed that the implementation of safety riding program for the students by Kampar Country Police in the implementation has been running smoothly, while in terms of resources are insufficient, including from human resources that still classified less.and from physical resources ie tools used in the implementation the safety riding program is still inadequate and lack of informationdelivery. Then executive officers whom still lack as obstacles in the implementation of safety riding program should be overcome by adding staff or executive staff. As for the students should have a high awareness of orderly passage and make safety a necessity in driving. Keywords: Policy, Implementation, Safety Riding, Student